Comparative Identification of Covid-19 Antibodies in COVID-19 PCR Positive Patients and its Correlation to Age Group: A Cross Sectional Study (Journal of Medical & Health Sciences Review, 2026)
The humoral immune response to SARS-CoV-2 infection varies among individuals, and age has been suggested as a potential factor influencing antibody development. Evaluating antibody presence in COVID-19 PCR-positive patients and its correlation with age is important for understanding immunity and guiding public health strategies. This study aimed to comparatively assess the development of COVID-19-specific antibodies using the immunochromatographic (ICT) method in PCR-confirmed COVID-19 patients and to analyze the association of antibody positivity with different age groups. A cross-sectional analytical study was conducted on 300 COVID-19 PCR-positive patients, divided into two age groups: Group A (18–40 years, n = 150) and Group B (41–65 years, n = 150). Blood samples were collected and tested for SARS-CoV-2-specific antibodies using the ICT method. Antibody positivity rates were calculated for each group, and the association between age and antibody development was evaluated using the Chi-square test of independence. Odds ratios (OR) and 95% confidence intervals (CI) were calculated to quantify the effect size. Antibody development was observed in 144 of 150 patients (96%) in the 18–40 age group and in 36 of 150 patients (24%) in the 41–65 age group. The Chi-square test indicated a highly significant association between age and antibody positivity (χ² = 162, df = 1, p < 0.001). Younger patients were significantly more likely to develop antibodies compared to older patients (OR = 76, 95% CI: 35.2–164.1). These findings suggest a strong age-dependent humoral response to SARS-CoV-2 infection, potentially influenced by immunosenescence and host factors. The ICT-based detection of SARS-CoV-2 antibodies revealed a statistically significant correlation between age and antibody development in COVID-19 PCR-positive patients, with younger adults demonstrating markedly higher seroconversion rates. These results highlight the importance of age as a determinant of post-infection immunity and may inform vaccination and public health strategies.